Natural repeated backcrosses lead to triploidy and tetraploidy in parthenogenetic butterfly lizards (Leiolepis: Agamidae) - Galoyan, Eduard; Nazarov, Roman; Altmanová, Marie; Matveevsky, Sergey; Kropachev, Ivan; Dedukh, Dmitrij; Iryshkov, Eugene; Pankin, Mark; Sopilko, Natalia; Nikolaev, Oleg; Orlov, Nikolai; Arakelyan, Marine; et al. (Scientific reports, 2025)
Obligatory parthenogenesis in vertebrates is restricted to squamate reptiles and evolved through hybridisation. Parthenogens can hybridise with sexual species, resulting in individuals with increased ploidy levels. We describe two successive hybridisations of the parthenogenetic butterfly lizards (genus Leiolepis) in Vietnam with a parental sexual species. Contrary to previous proposals, we document that parthenogenetic L. guentherpetersi has mitochondrial DNA and two haploid sets from L. guttata and one from L. reevesii, suggesting that it is the result of a backcross of a parthenogenetic L. guttata × L. reevesii hybrid with a L. guttata male increasing ploidy from 2n to 3n. Within the range of L. guentherpetersi, we found an adult tetraploid male with three L. guttata and one L. reevesii haploid genomes. It probably originated from fertilisation of an unreduced triploid L. guentherpetersi egg by a L. guttata sperm. Although its external morphology resembles that of the maternal species, it possessed exceptionally large erythrocytes and was likely sterile. As increased ploidy level above triploidy or tetraploidy appears to be harmful for amniotes, all-female asexual lineages should evolve a strategy to prevent incorporation of other haploid genomes from a sexual species by avoiding fertilisation by sexual males.
Keywords: Lizards; Parthenogenesis; triploidie; Vietnam; mužské pohlaví; Inbreeding; ještěři; DNA, Mitochondrial; Leiolepis; inbreeding; partenogeneze; ženské pohlaví; zvířata; Meiosis; mitochondriální DNA; Hybridization, Genetic; tetraploidie; hybridizace genetická; Tetraploidy; Triploidy; Female; Male; Hybridisation; Animals